2004
DOI: 10.1038/sj.onc.1207149
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ErbB2 enhances radiation-induced NF-κB activation

Abstract: Her-2/neu (ErbB2) oncogene, the second member of the epidermal growth factor receptor (EGFR) family, encodes a transmembrane tyrosine kinase receptor in Her-2-positive tumors. Accumulating evidences demonstrate that signaling networks activated by EGFR and transcription factor NFjB are associated with cell response to ionizing radiation (IR). The present study shows that overexpression of ErbB2 enhanced NF-jB activation induced by IR in human breast carcinoma MCF-7 cells transfected with ErbB2 genes (MCF-7/Erb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 60 publications
2
77
0
1
Order By: Relevance
“…NF-κB is a transcription factor that plays a key role in tumor radioadaptive resistance. It has been reported that DNA binding of NF-κB was activated by IR (31,32) and was regulated by various signaling cascades, e.g., the TNF-α pathway, Ras-PI3K-Akt pathway, and Ras-MAPK pathway (33)(34)(35)(36). In addition, several genes, such as the anti-apoptotic Bcl family, cyclin B1, cyclin D2, superoxide dismutases (SOD) that suppress ROS generation and HER-2, were identified as effector genes of NF-κB and these upregulated both cell proliferation and viability (21).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a transcription factor that plays a key role in tumor radioadaptive resistance. It has been reported that DNA binding of NF-κB was activated by IR (31,32) and was regulated by various signaling cascades, e.g., the TNF-α pathway, Ras-PI3K-Akt pathway, and Ras-MAPK pathway (33)(34)(35)(36). In addition, several genes, such as the anti-apoptotic Bcl family, cyclin B1, cyclin D2, superoxide dismutases (SOD) that suppress ROS generation and HER-2, were identified as effector genes of NF-κB and these upregulated both cell proliferation and viability (21).…”
Section: Discussionmentioning
confidence: 99%
“…In various tumour specimens from cancer patients a high correlation between EGFR overexpression and NF-kB activation can be demonstrated (Tang et al, 2006;Van Laere et al, 2007). Interestingly, several pre-clinical studies using receptor-targeting strategies suggest that interference with EGFR signalling reduces NF-kB activity (Sclabas et al, 2003;Guo et al, 2004;Chinnaiyan et al, 2005;Damiano et al, 2006;Singh et al, 2007). Constitutive or deregulated NF-kB activation is observed in malignant cell types from different origin and is believed to contribute to tumourigenesis by its ability to inhibit apoptosis and to enhance cell proliferation (Keutgens et al, 2006;Pacifico and Leonardi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas studies in clinical breast cancer series have documented an inverse relationship between the levels of HER-2 and Bcl-2 expression (30,31), mechanistic studies have shown that HER-2 gene transfer into MCF-7 breast cancer cells strongly up-regulates Bcl-2 and Bcl-X L expression (32,33) and that AS-mediated HER-2 down-regulation also suppresses Bcl-2 expression (23). The purpose of the present study was to assess whether HER-2 blockade by trastuzumab attenuates Bcl-2/ Bcl-X L expression and increases the susceptibility of breast cancer cells to apoptosis induction.…”
Section: Introductionmentioning
confidence: 99%